Constructing and validating a Code of Ethics in Testing Inventory: investigating EFL instructors’ perspectives - Mansooreh Hosseinnia; Zahra Kafi (Language Testing in Asia)
Abstract As testing involves various aspects of education as well as the ones who are involved like instructors, students, managers, teacher trainers, testers, and decision-makers, it comes to be highly crucial to develop ethical tests. In addition, as some methods of testing are more favored and practiced compared to others without considering the ethical issues behind them, providing the members involved in the educational process with a set of code of ethics in testing will hand them with a clear-cut framework to develop ethical tests accordingly. The major purpose of the present study was to construct a Code of Ethics Inventory for testing. To this end, a questionnaire was designed by selecting the most influential factors of ethical issues in language testing. Utilizing a mixed-method approach, a total of 255 Iranian EFL teachers were rated with this questionnaire, and a number of them took part in the interview process. For checking the construct validity of the questionnaire, Exploratory Factor Analysis (EFA) with principal component analysis and varimax rotation was employed. In addition, to examine the validity of the Code of Ethics Scale, Confirmatory Factor Analysis was used. Besides, the reliability of the inventory was estimated by running Cronbach’s alpha. As an alternative to the traditional approach, this study employed structural equation modeling (SEM) with multiple indicators to examine the validity and reliability of Codes of Ethics in Testing Inventory. The reliability of the inventory gained a good reliability coefficient of 0.816. Also, after employing EFA, the final version of the inventory had 70 items with eight categories or factors. Some items were excluded from a couple of categories because of loadings less than 0.30. The results of the qualitative phase were also thoroughly discussed in the Results section. The limitations and shortcomings of the undertaken study could be considered as departures for further research. Also, the implications were presented in the context of English language teaching.